Prospek Diplomasi Indonesia dalam Kerjasama Selatan-Selatan: Refleksi Teoritis Kajian Kapitalisme Konsumen di Era Susilo Bambang Yudhoyono - Falahi, Ziyad (UI Scholars Hub, 2018)
This paper analyzes the consumer capitalism in Susilo Bambang Yudhoyono's administration and its influence to Indonesian diplomacy. Study of consumer capitalism is relevant in analyzing the case of South-South cooperation that reflects new model of international division of labor. Consumer capitalism divides Southern countries into two types, producers, such as China, India, Brazil, and Russia, and consumers, such as Indonesia. Indonesian government's plan to be vital part of South-South Cooperation needs to be requestioned, considering Indonesia's economy that heavily relied on consumption. Consumer capitalism can become a buffer of the Indonesian economy to face the 2008 global crisis, but its implications in the future will only marginalized Indonesia.